The hunchback heuristic: do people associate anger with low status and calmness with high status? - Weerabangsa, Mass Misha'ari (2021)
This thesis proposes the existence of a ‘hunchback heuristic’ (HBH): a tendency to associate members of low status social groups with anger and related behaviours, and members of high status social groups with calmness. A series of experiments were conducted to investigate the existence, boundary conditions, effects and interactions of this novel construct.